Top–down modulation of prepulse inhibition of the startle reflex in humans and rats - Li, Liang; Du, Yi; Li, Nanxin; Wu, Xihong; Wu, Yanhong (Neuroscience and biobehavioral reviews, 2009)
Prepulse inhibition (PPI) is the attenuation of the startle reflex when the sudden intense startling stimulus is shortly preceded by a weaker, non-startling sensory stimulus (prepulse). PPI reflects a protective function of reducing disruptive influences to the processing of prepulse signals and is recognized as a model of sensorimotor gating. In humans, PPI is modulated by both attentional and emotional responses to prepulse, indicating that this early-stage gating is top–down modulated by higher-order cognitive processes. Recent studies have confirmed top–down modulation of PPI in animals, because PPI in rats is enhanced by auditory fear conditioning and perceived separation between fear-conditioned prepulse and masker. This review summarizes recent studies of top–down modulation of PPI conducted in humans and those in rats. Since both baseline PPI and attentional modulation of PPI in patients with schizophrenia are impaired, and both baseline PPI and conditional modulation of PPI in rats with isolation rearing are impaired, this review emphasizes that investigation of top–down modulation of PPI is critical for establishing new animal models for studying both cognitive features and neural bases of schizophrenia. Deficits in either baseline PPI or attentional modulation of PPI in either patients with attention-deficit/hyperactivity disorder (ADHD) or ADHD-modeling rats are also discussed.